Modification of calcium-based catalyst derived from natural sources for palm oil biodiesel production - Che Mohamad, Nur Aqlili Riana (2015)
In recent years, calcium oxide has gained much interest among researchers in the production of biodiesel due to its high catalytic activity compared to other solid heterogeneous catalysts. Interestingly it also can be produced from natural abundant material that is cheap and readily available. In this study, various types of natural calcium sources such as cockle shells, horned helmet shells, limestone and mud creeper shells were selected and used to synthesize active calcium oxide catalyst for biodiesel production. The catalytic activity of calcined CaO catalyst was further improved by modification using hydration technique. This facile and economical technique was conducted in reflux condition using different medium such as distilled water, ammonia hydroxide solution and sodium hydroxide solution. The physicochemical characteristics of the raw material and synthesized catalysts was investigated using various characterization methods such as X-Ray Fluorescence (XRF), Thermogravimetric analysis (TGA), X-Ray Diffraction (XRD), Brunauer-Emmett-Teller (BET) surface area analysis, CO2-Temperature Programmed Desorption (CO2-TPD) and Field Emission Scanning Electron Microscopy (FESEM). For catalytic activity, all of the modified and unmodified catalysts were tested for the transesterification of palm oil under reaction condition of 15:1 methanol to oil ratio, 3 wt.% catalyst loading, 5 h reaction time at 338 K reaction temperature. The product (FAME) was analysed by using Gas Chromatography (GC) and Atomic Absorption Spectroscopy (AAS) was used to identify the amount of Ca leaching. As expected, all of the modified catalysts show significantly higher biodiesel conversion compared to that of pure CaO catalysts, while distilled water can be regarded as the best medium for hydration technique compared to ammonia hydroxide solution and sodium hydroxide solution generally. Hydrate limestone (i.e.: in distilled water, HLS) shows the highest biodiesel conversion of 98 %, while the lowest biodiesel conversion of 67 % was recorded when the mud creeper shells was modified in sodium hydroxide solution (OSS). In general, the improvement in the catalytic activity can be attributed to the increase in the basic sites and changes in morphology of the modified catalysts. The evaluation of the fuel properties according to the international standard of EN 14214 and ASTM D 6751 revealed that the produced biodiesel has meet certain requirements for biodiesel (B100) and has a potential to be used as blending fuel.